Empowerment of Persons with Disabilities inIndia: With Special Reference to Uttar Pradesh - Alendra Tripathi and Dr. A. P. Bharti (International journal of economic perspectives, 2022)
Disabled persons are the most marginalized and suffer from social deviations, stigma and social exclusion and oppression. Government of India and the Government of Uttar Pradesh have launched several schemes in the last decades. The plans are well thought out and supported by financial support. The state has all the structures and processes that are necessary to implement these programs. The ultimate objective of these schemes is the upliftment and empowerment of people with disabilities. In view of the problems of differently abled persons in Uttar Pradesh and the government's concern for their empowerment and development, it is mandatory to examine the pattern of development of public spending on the development of persons with disabilities in Uttar Pradesh. Present paper attempts to review the government schemes for empowerment of PWDs in the state of Uttar Pradesh.